Treatment of pulmonary hypertension associated with COPD: a systematic review. Issue 1 (21st February 2022) - Arif, Ragdah; Pandey, Arjun; Zhao, Ying; Arsenault-Mehta, Kyle; Khoujah, Danya; Mehta, Sanjay
Chronic obstructive pulmonary disease-associated pulmonary hypertension (COPD-PH) is an increasingly recognised condition which contributes to worsening dyspnoea and poor survival in COPD. It is uncertain whether specific treatment of COPD-PH, including use of medications approved for pulmonary arterial hypertension (PAH), improves clinical outcomes. This systematic review and meta-analysis assesses potential benefits and risks of therapeutic options for COPD-PH. We searched Medline and Embase for relevant publications until September 2020. Articles were screened for studies on treatment of COPD-PH for at least 4 weeks in 10 or more patients. Screening, data extraction, and risk of bias assessment were performed independently in duplicate. When possible, relevant results were pooled using the random effects model. Supplemental long-term oxygen therapy (LTOT) mildly reduced mean pulmonary artery pressure (PAP), slowed progression of PH, and reduced mortality, but other clinical or functional benefits were not assessed. Phosphodiesterase type 5 inhibitors significantly improved systolic PAP (pooled treatment effect −5.9 mmHg; 95% CI −10.3, −1.6), but had inconsistent clinical benefits. Calcium channel blockers and endothelin receptor antagonists had limited haemodynamic, clinical, or survival benefits. Statins had limited clinical benefits despite significantly lowering systolic PAP (pooled treatment effect −4.6 mmHg; 95% CI −6.3, −2.9). This review supports guideline recommendations for LTOT in hypoxaemic COPD-PH patients as well as recommendations against treatment with PAH-targeted medications. Effective treatment of COPD-PH depends upon research into the pathobiology and future high-quality studies comprehensively assessing clinically relevant outcomes are needed. The presence of PH in COPD patients is associated with worsening morbidity and mortality. These findings support guideline recommendations for LTOT in hypoxaemic COPD-PH patients as well as recommendations against treatment using PAH-targeted medications. https://bit.ly/3Al4rLb